GROWTH AND CONDITION FACTOR OF RAINBOW SELEBENSIS (Tolmdherina celebensic Boulenger) lN LAKE TOWUTI, SOUTH CELEBES - Syahroma Husni Nasution (Research Center for Fisheries, 2007)
Rainbow selebensis (Telmatherina celebensis) is Telmatherinidae family and endemic species in Lake Towuti. This species has beautiful color, potential to be ornamental fishes. The aim of this research is to study growrth and condition factor of the fish, as a basic information for fish conservation.